Avaliação crítica da política de transporte público em Fortaleza: análise do sistema integrado de transporte a partir do Terminal Parangaba - Cazé, Ledervan Vieira (2014)
This evaluative research questions the public policy of urban transport in the city of Fortaleza, intending to realize its efficiency, quality and impacts on the target population in order to support a rethinking of public transport as a service that truly leverages the need to go worthily and come free of the citizen. To do so, performs the review, organization, analysis and interpretation of theoretical texts, statistics, numbers, and official publications of the bodies that have the concession to manage their service, thereby formulating its institutional design. The Public Transportation in Fortaleza, in the chaos set lacks break with the prevailing political and administrative matrix promoting new ways developed from a sociological conception, since mobility is ambivalent, but takes the form of social relations; be mobile does not necessarily mean moving quickly.